Inventing the Israelite : Jewish Fiction in Nineteenth-Century France. - Samuels, Maurice (Stanford studies in Jewish history and culture., 2009)
This book brings to light the first Jewish fiction in French and reveals how the first generation of Jews born as French citizens used fiction as a laboratory for experimenting with modern forms of Jewish identity.